Novel Tetracycline Resistance Gene, tet(32), in the Clostridium-Related Human Colonic Anaerobe K10 and Its Transmission In Vitro to the Rumen Anaerobe Butyrivibrio fibrisolvens - Melville, Claire M. (American Society for Microbiology, 2001)
A novel tetracycline resistance gene, designated tet(32), which confers a high level of tetracycline resistance, was identified in the Clostridium-related human colonic anaerobe K10, which also carries tet(W). tet(32) was transmissible in vitro to the rumen anaerobe Butyrivibrio fibrisolvens 2221(R). The predicted gene product of tet(32) has 76% amino acid identity with Tet(O). PCR amplification indicated that tet(32) is widely distributed in the ovine rumen and in porcine feces.